2000
DOI: 10.1103/physrevlett.84.4653
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Surface Vibrational Spectroscopy of CO Adsorbed on Ru(001) during Desorption

Abstract: Using time-resolved sum-frequency generation spectroscopy, the C-O stretch vibration of carbon monoxide adsorbed on a single-crystal Ru(001) surface is investigated during femtosecond near-IR laser excitation leading to desorption. A large transient redshift, a broadening of the resonance, and a strong decrease in intensity are observed. These originate from coupling of the C-O stretch to low-frequency modes, especially the frustrated rotation, that are highly excited in the desorption process. PACS numbers: 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
184
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 178 publications
(192 citation statements)
references
References 23 publications
6
184
1
1
Order By: Relevance
“…The low-frequency shift and the broadening of the CO spectra at a delay of 0 ps suggest that the low-frequency modes of adsorbed CO, that is, stretching, frustrated rotation, and frustrated translation modes of Pt-CO, were thermally excited by pump pulses, as reported by Bonn et al 32 Thus, it is concluded that the transient site migration of adsorbed CO on the Pt surface was caused by a transient rise in the surface temperature of Pt induced by pump pulses.…”
Section: Resultssupporting
confidence: 68%
“…The low-frequency shift and the broadening of the CO spectra at a delay of 0 ps suggest that the low-frequency modes of adsorbed CO, that is, stretching, frustrated rotation, and frustrated translation modes of Pt-CO, were thermally excited by pump pulses, as reported by Bonn et al 32 Thus, it is concluded that the transient site migration of adsorbed CO on the Pt surface was caused by a transient rise in the surface temperature of Pt induced by pump pulses.…”
Section: Resultssupporting
confidence: 68%
“…2(c). The temporal evolution of the spectroscopic features resembles the transient responses observed with vibrational spectroscopy for CO that were interpreted as a heating of the molecule leading to diffusion [1] or desorption [2][3][4] largely driven by frustrated rotations, that typically couple to the electron system on a subpicosecond time scale [1,27]. The apparent stronger interaction evidenced by the increasingd intensity and the redshift with intensity lowering of the 2~Ã indicates that the majority of CO molecules moves away from the on-top site towards more highly coordinated bridge and hollow sites [8,22].…”
Section: Prl 110 186101 (2013) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 96%
“…This technique has been successfully utilized, e.g., to monitor transient excitation of external adsorbate vibrational modes that couple to diffusion [1] and to desorption reactions [2][3][4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally produced by mechanically actuated choppers or valves, pulse durations are limited to a few ms. Just as ultrashort light and electron pulses have become central tools for a wide variety of dynamical studies in physics, chemistry and biology [5][6][7][8][9][10][11] , non-mechanical approaches to produce much shorter pulses of neutral atoms and molecules offer fascinating new experimental possibilities. Timing experiments of all kinds initiated by bimolecular collisions become possible, for example, direct lifetime measurements of bimolecular collision complexes (the lifetimes of collision complexes can be indirectly inferred from scattering angular distributions.…”
mentioning
confidence: 99%